Hydrogeology of the Krafla geothermal system, northeast Iceland. Issue 1 (21st May 2015) - Pope, E. C.; Bird, D. K.; Arnórsson, S.; Giroud, N.
Abstract: The Krafla geothermal system is located in Iceland's northeastern neovolcanic zone, within the Krafla central volcanic complex. Geothermal fluids are superheated steam closest to the magma heat source, two‐phase at higher depths, and sub‐boiling at the shallowest depths. Hydrogen isotope ratios of geothermal fluids range from −87‰, equivalent to local meteoric water, to −94‰. These fluids are enriched in 18 O relative to the global meteoric line by +0.5–3.2‰. Calculated vapor fractions of the fluids are 0.0–0.5 wt% ( 0–16% by volume) in the northwestern portion of the geothermal system and increase towards the southeast, up to 5.4 wt% ( 57% by volume). Hydrothermal epidote sampled from 900 to 2500 m depth has δD values from −127 to −108‰, and δ 18 O from −13.0 to −9.6‰. Fluids in equilibrium with epidote have isotope compositions similar to those calculated for the vapor phase of two‐phase aquifer fluids. We interpret the large range in δDEPIDOTE and δ 18 OEPIDOTE across the system and within individual wells (up to 7‰ and 3.3‰, respectively) to result from variable mixing of shallow sub‐boiling groundwater with condensates of vapor rising from a deeper two‐phase reservoir. The data suggest that meteoric waters derived from a single source in the northwest are separated into the shallow sub‐boiling reservoir, and deeper two‐phase reservoir. Interaction between these reservoirs occurs by channelized vertical flow of vapor along fractures, and input of magmatic volatiles further alters fluid chemistry in some wells. Isotopic compositions of hydrothermal epidote reflect local equilibrium with fluids formed by mixtures of shallow water, deep vapor condensates, and magmatic volatiles, whose ionic strength is subsequently derived from dissolution of basalt host rock. This study illustrates the benefits of combining phase segregation effects in two‐phase systems during analysis of wellhead fluid data with stable isotope values of hydrous alteration minerals when evaluating the complex hydrogeology of volcano‐hosted geothermal systems. Abstract : Geothermal fluids in the Krafla geothermal system, northeast Iceland, have been characterized using oxygen and hydrogen isotopes, CO2 content, vapor content and temperature, and compared with hydrogen and oxygen isotope compositions of fluids that would be in equilibrium with hydrothermal epidote sampled from producing geothermal wells. We propose that vapor, rising from a two‐phase aquifer close to the magma heat source, variably mixes with the primary producing aquifer at 1000 m depth, producing the observed heterogeneity in fluid properties across the geothermal system.